How Attention and Strategies Shape Math Anxiety in Children - He, Yuwei; Wang, Rong; Wang, Ting; Duan, Suyi (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This study explores the bidirectional relationship between attentional biases, emotional regulation, and math anxiety. It highlights how sustained attentional states, influenced by attentional control deficits, contribute to anxiety and impaired mathematical performance. The article reviews the stability of attentional behavior and its long-term effects, discussing innovative computational models and intervention strategies. It emphasizes the need for addressing attentional control deficits to break the cycle of math anxiety and improve both emotional well-being and mathematical performance.